A Small-Molecule Inhibitor of Bax and Bak Oligomerization Prevents Genotoxic Cell Death and Promotes Neuroprotection. Issue 4 (20th April 2017) - Niu, Xin; Brahmbhatt, Hetal; Mergenthaler, Philipp; Zhang, Zhi; Sang, Jing; Daude, Michael; Ehlert, Fabian G.R.; Diederich, Wibke E.; Wong, Eve; Zhu, Weijia; Pogmore, Justin; Nandy, Jyoti P.; et al.
Summary: Aberrant apoptosis can lead to acute or chronic degenerative diseases. Mitochondrial outer membrane permeabilization (MOMP) triggered by the oligomerization of the Bcl-2 family proteins Bax/Bak is an irreversible step leading to execution of apoptosis. Here, we describe the discovery of small-molecule inhibitors of Bax/Bak oligomerization that prevent MOMP. We demonstrate that these molecules disrupt multiple, but not all, interactions between Bax dimer interfaces thereby interfering with the formation of higher-order oligomers in the MOM, but not recruitment of Bax to the MOM. Small-molecule inhibition of Bax/Bak oligomerization allowed cells to evade apoptotic stimuli and rescued neurons from death after excitotoxicity, demonstrating that oligomerization of Bax is essential for MOMP. Our discovery of small-molecule Bax/Bak inhibitors provides novel tools for the investigation of the mechanisms leading to MOMP and will ultimately facilitate development of compounds inhibiting Bax/Bak in acute and chronic degenerative diseases. Highlights: Discovery of novel small-molecule inhibitors of Bax and Bak oligomerization Compounds provide evidence that monomeric Bax/Bak is insufficient for MOMP Compounds prevent Bax/Bak oligomerization at specific dimer sites Compounds prevent cell death and mediate neuroprotection after excitotoxicity Abstract : Niu et al. identified novel small-molecule inhibitors of pro-apoptotic Bax and Bak oligomerization which allow cells to resist apoptosis and that protect neurons from excitotoxicity, providing novel tools for preclinical target evaluation and drug development in degenerative diseases.